Fasting experience of patients with Type 2 diabetes mellitus on insulin therapy during Ramadan: VISION Ramadan substudy. (May 2019) - Jabbar, Abdul; Wan Mohamed, Wan Mohd Izani; Spaepen, Erik; Reed, Victoria; Tayeb, Khaled; Assaad Khalil, Samir H.; Treuer, Tamas; Bhattacharya, Indranil
Abstract: Aims: To describe the characteristics and fasting experience of a subgroup of patients in the VISION study who initiated insulin therapy and chose to fast during Ramadan, and to discuss the VISION Ramadan substudy data in the context of previous Ramadan studies. Methods: The VISION study was a prospective, non-interventional, observational study of adult patients with Type 2 diabetes mellitus in 6 countries in the Western Pacific, Middle East and North Africa, receiving insulin injection therapy for the first time. In this VISION Ramadan substudy, fasting data was collected during Ramadan 2014 and 2015. Results: Of 1617 patients in the VISION study, data was collected for 357 patients who chose to fast during Ramadan. At baseline, mean HbA1c was 10.1%, duration of diabetes was 8.8 years, and mean BMI was 30 kg/m 2 . All patients with non-missing data (n = 169) received advice on fasting during Ramadan. The majority of patients fasted for the full month of Ramadan, and around one-third of patients fasted outside Ramadan. Conclusions: Here we provide an update on the characteristics and Ramadan experience of patients with Type 2 diabetes mellitus who initiated insulin therapy and chose to fast during Ramadan. There is still a need to explore patient's experience during fasting, and identify and address methods to better help manage those patients.